Bearing capacity improvement using soil-filled post-consumer PET bottles. Issue 3 (18th June 2022) - Moghaddas Tafreshi, S. N.; Rafiezadeh Malekshah, A.; Rahimi, M.; Dawson, A.R.
Abstract : This study proposes reusing post-consumer soil-filled PET (polyethylene terephthalate) bottles as a novel soil reinforcing element by conducting a laboratory-scale experimental investigation. The concept is that the polymer bottle walls act to confine the interior soil so that the bed behaves somewhat like a brick-built load spreading zone. The soil-filled bottles were horizontally laid within the soil bed in the desired depth and then the backfilling was performed. The effect of different parameters such as depth of placement, width and height of the soil-filled, bottle-reinforced mattress are studied under static plate load testing. Test results revealed that the bottle-reinforced bed is highly rigid, delivering very high bearing capacities at small soil displacements. Optimum depth of placement, width and height of the bottle-reinforced zone were respectively about 0.03 B, 2.17 B and 0.57 B . An improvement in bearing capacity ratio (BCR) by a factor of ∼3, and up to 80% reduction in soil settlement, were observed. The proposed method of soil reinforcement can be an excellent and relatively economic alternative to conventional geosynthetic reinforcement, as well as delivering geotechnical and environmental advantages.